Phylogenetic characteristics and analysis of the antigenic epitopes of Russian rotaviruses in comparison with vaccine strains - T. A. Sashina; O. V. Morozova; E. I. Velikzhanina; N. V. Epifanova; N. A. Novikova (Инфекция и иммунитет)
Accumulation of mutations in the amino acid sequence of immunologically significant regions of the outer capsid proteins in locally circulating rotaviruses may reduce the effectiveness of vaccine-generated protection. The aim of the work was to comparatively analyze Russian rotaviruses and strains of the Indian pentavalent vaccine approved for use in the Russian Federation in 2020.